Pelatihan dan Pendampingan Penyusunan PTK untuk Meningkatkan Kemampuan Menulis Guru SD 4 Karangmalang - Sumaji, Sumaji; Rahayu, Ratri; Bintoro, Henry Suryo; Wanabuliandari , Savitri (Jurnal SOLMA, 2025)
Background: The low quality of education can be improved by fixing existing problems in the learning process, one of which is that teachers can carry out classroom action research activities. Therefore, this service team provides training in preparing PTK which aims to mobilize, direct, provide appropriate technology that can encourage teachers to design and create PTK. Method: The method used was lecture, question and answer, discussion, exchange of opinions and practice using audience centered techniques to SD 4 Karangmalang teachers consisting of 9 teachers and 1 principal. Results: Through this service activity, teachers are able to understand strategies in preparing PTK. Conclusion: Apart from that, this activity is expected to improve teachers' writing skills.